Republic of Poland : Detailed Assessment of Observance of Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2012)
The 2008 transition to the new banking supervisory framework in Poland has been relatively smooth, and the banking system has proven effective in weathering the financial crisis. This assessment focuses on the working of the Polish Financial Supervision Commission (KNF), which is responsible for banking supervision in Poland. KNF has undertaken numerous proactive measures to preserve financial sector stability during the crisis. As a priority, KNF's interaction with bank auditors as well as with supervisory board members should also be strengthened.